BERHENTI BEKERJA DEMI KELUARGA: Dilema Perempuan Karir Dalam Perspektif Feminisme - Endah Siswati (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2020)
Women generally face a dilemma when they have to choose between work or family. Women must go through long contemplations and experience inner struggles before coming to a decision to choose between the two; keep working or become a housewife. Patriarchal culture, familial ideology, the various consequences that must be faced from a decision, and psychological facts sharpen the dilemma. This paper tries to explore this problem from the perspective of feminism, especially liberal feminism. The focus of the discussion is upper middle class women and is not intended to generalize problems to other socioeconomic classes.